2013
DOI: 10.1037/a0031255
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and motivation on cognitive effort: Implications for cognitive engagement in older adulthood.

Abstract: We examined age differences in the effort required to perform the basic cognitive operations needed to achieve a specified objective outcome and how hypothesized increases in effort requirements in later life are related to intrinsic motivation associated with enjoyment of and participation in effortful cognitive activities. Young (N = 59; 20–40 years) and older (N = 57; 64–85 years) adults performed a memory-search task varying in difficulty across trials, with systolic blood pressure responsivity—calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 56 publications
13
111
1
5
Order By: Relevance
“…For example, Hess and Ennis (2012) found stronger SBP responses in older adults during both a fatigue induction period in which participants were presented a simple or complex counting challenge and an ensuing fatigue influence period in which participants solved multiplication problems. In a follow-up, Ennis et al (2013) found higher difficulty appraisals and stronger SBP responses in older adults responding to a Sternberg (1966) type memory task whose difficulty was varied across trial blocks. They also found that older adults (1) displayed greater reductions in SBP responses at higher difficulty levels and (2) evinced SBP responses that were more sensitive to rated success importance.…”
Section: Age-related Cognitive Declinementioning
confidence: 94%
See 1 more Smart Citation
“…For example, Hess and Ennis (2012) found stronger SBP responses in older adults during both a fatigue induction period in which participants were presented a simple or complex counting challenge and an ensuing fatigue influence period in which participants solved multiplication problems. In a follow-up, Ennis et al (2013) found higher difficulty appraisals and stronger SBP responses in older adults responding to a Sternberg (1966) type memory task whose difficulty was varied across trial blocks. They also found that older adults (1) displayed greater reductions in SBP responses at higher difficulty levels and (2) evinced SBP responses that were more sensitive to rated success importance.…”
Section: Age-related Cognitive Declinementioning
confidence: 94%
“…Recently, Hess and colleagues applied aspects of the ability analysis above to address questions pertaining to effort and CV responsiveness in older adults (Ennis et al, 2013;Hess, 2014;Hess andEnnis, 2012, 2014;Smith and Hess, 2015). They reasoned that, due to normal (i.e., asymptomatic), age-related declines in cognitive function, older adults should find it more difficult to initiate and maintain cognitive performance.…”
Section: Age-related Cognitive Declinementioning
confidence: 95%
“…Subjective task difficulty has been shown to be related to effort expenditure (Ennis, Hess & Smith, 2013). Those who experienced the high task-related effort as less effortful would require less cognitive resources to maintain the effort manipulation.…”
Section: Effort Disrupts Implicit Agency 29mentioning
confidence: 99%
“…There is no doubt that cognitive aging is a multifaceted process and that holistic individually tailored treatments are likely more effective than generic single-track interventions [e.g., Bredesen, 2014]. Individual factors (as well as sociocultural factors) that may play important roles in cognitive aging and intervention efficacy include (but are not limited to) personality [e.g., openness, Sharp et al, 2010], initial motivation/interest [e.g., Ennis, Hess, & Smith, 2013], level and type of reinforcement required, cultural factors [e.g., Park & Gutchess, 2006], socioeconomic status, and education level. Cognitive interventions including our six factors may have cascading effects on these other factors.…”
Section: Theoretical Considerationsmentioning
confidence: 99%